The use of the self-selected rest interval method is as effective for optimizing post-activation performance enhancement in elite athletes as employing the best fixed rest interval - Lima, L.; Barreto, R.; Junior, R.; Fontanetti, G. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Responsiveness to post-activation performance enhancement (PAPE) has been extensively investigated and shown to be modulated by factors relating to an individuals inherent characteristics (e.g., fiber type distribution, biological sex or age) and previous history with exercise (e.g., training status or the manifestation of exercise-induced muscle damage) or to pre-activation (PA) protocol-related factors (e.g., load, number of sets and repetitions or the rest interval between PA and performance assessment). Addressing the former, recent research indicated that trained individuals exhibit greater PAPE responsiveness using a self-selected recovery interval (SSI) compared to a fixed four-minute recovery interval (FRI), which negatively affected performance. However, comparing PAPE responsiveness using a single FRI and SSI might be misleading, as optimal recovery intervals can vary among individuals. This study aimed to investigate whether adopting SSI is more effective in inducing PAPE than utilizing five different fixed recovery intervals (FRI) and the individual`s best recovery interval. METHODS: After familiarization with countermovement jump (CMJ) exercises and determining the load for five-repetition maximum (5RM: 146 ± 27 kg) squat exercise, ten male professional volleyball athletes (20.6 ± 1.5 years; 92.8 ± 4.9 kg; 195 ± 8 cm) from Brazil`s national youth league participated in three randomly order experimental sessions: 1) control session (CON), with measurement of CMJ height 4 minutes before and 2, 4, 6, 8, and 10 minutes after participants rested without PA; 2) session with FRI, with measurement of CMJ height at 2, 4, 6, 8 and 10 minutes after performing a PA exercise consisting of five squats with 5RM load (the best recovery interval during this session was also considered by identifying the time-point at which each participant achieved the greatest CMJ height); and 3) session with SSI, with measurement of CMJ height once after performing the PA with a SSI based on a readiness scale. CMJ height values recorded at all time-points were compared to values recorded at baseline in the CON session using one-way ANOVA followed by Bonferronis post hoc tests. RESULTS: No significant differences were observed between CMJ heights registered in the CON session. CMJ height was higher (p < 0.05) than the baseline measurement at minutes 4, 6, and 8 post-PA in the FRI session, for the best individual recovery interval during the FRI session, and after the PA in the SSI session. No significant differences were found between the CMJ heights of the best individual recovery interval in the FRI session (49.2 ± 6.8 cm at 315 ± 89 seconds post-PA) and post-PA in the SSI session (49.6 ± 6.6 cm at 213 ± 63). CONCLUSION: Adopting FRI and SSI are equally effective in inducing PAPE in elite athletes. Despite being as effective as adopting FRI to induce PAPE, SSI is more intuitively applicable in contexts where PAPE is implemented.